Uji Performansi Mesin Penepung Tipe Palu (Hammer Mill) Untuk Penepungan Hotong (Setaria Italica L.) - Sutejo, Agus; Kurniasari, Rahma Sholihah; Wicaksono, Dionisius Dwi (abe.fp.unila.ac.id, 2023)
Indonesia has a high source of biodiversity but consumption patterns still depend on rice as a basic food needs containing carbohydrates. Food diversification needs to be done to achieve food diversification, especially plants that can grow on dry land such as hotong plants. Hotong is a plant that grows a lot in Indonesia but still has postharvest constraints on the flouring process. Therefore, the study was conducted to determine the performance of hammer mill machine and compare with disc mill. The research was conducted in PT. Daud Teknik Maju Pratama in July 2022 with materials used 500 grams each on each test. The rotational speed tested on the hammer machine is 2887 rpm, 3608 rpm, and 4330 rpm, while the disc mill machine is 4485 rpm. The test was carried out one pass with three repetitions for each sample and the quality of flouring was tested using an 80 mesh. Performance test results showed the highest capacity of using hammer mill machine 4330 rpm, while the highest yield and the lowest scattered shrinkage using disc mill. Furthermore, the flour milling using both machines sifted using mesh 80 and flour that passes more produced from milling hammer mill machine 4330 rpm of 45.111%. The power required by the hammer mill machine to milling 500 grams of hotong is 5107,34 watts.Keywords: disc mill, hammer mill, hotong, milling